Solar radio burst type II and III with half wave dipole antenna / Farah Aqilah Mohd Pauzi - Farah Aqilah , Mohd Pauzi (2020)
An investigation into the physics of solar radio burst type II was done to understand the frequency gap between its fundamental and harmonic emissions that happen as aftershocks of Coronal Mass Ejection (CME). Up until now, the evolution of type II and its associated coronal wave still remain a mystery. Hazardous CME study upholds its fore coming danger to human and technology. This work also addresses the issue of the lack of spatial resolution of previous solar radio burst type II studies. An instrument produced by ETH Zürich namely the Compound Astronomical Low-cost Low-frequency Instrument for Spectroscopy and Transportable Spectrometers (CALLISTO) was used. A newly designed low frequency antenna array produced through a collaboration between University of Malaya (UM) and the Yunnan Astronomical Observatory (YNAO) of China named the Half Wave Dipole Antenna (HWDA) array is also used in this research. This dissertation describes the newly designed proposed instrument and its significance in studying solar radio burst type II. Comparison study is also made with other leading radio solar monitoring instruments such as the CALLISTO, Chinese Spectral Radio Heliograph (CSRH) and Murchison Widefield Array (MWA). Upon setting up the HWDA, the radio frequency interference (RFI) of the observation site in UM is shown to emphasize the suitability of the selected candidate site. Furthermore, it also includes the optimal observation design and strategies for future detection. This dissertation shows the preliminary results of the proposed instrument by detecting solar radio burst type III confirmed by CALLISTO. The same event also indicates a correlation ratio of 0.94 with that coincides with solar flare class C 2.0. Gopalswamy power law and the electron density were used to estimate the density scale height (Ln). At the bandpass frequency of the HWDA Ln was found to be 1.41 x 108 m. The calculated shock speeds are hence found to be 2.350 x 103 ms-1 and 1.504 x 107 ms-1 for low and high drift rates, respectively. These shock speed values indicate that the kilometric type II associated with CMEs are able to drive shocks only when it reaches far into the interplanetary medium.